Assessment of Dynamic Effects of Wave Loads in Fatigue Analysis for Fixed Steel Offshore Structures - Dinh Quang Cuong; Bui The Anh (Civil Engineering Journal, 2023)
This paper presents an algorithm and develops a formula to evaluate the dynamic effect of wave loading on fixed steel offshore structures (jacket structures) through the fatigue damage ratio. Applying the algorithm and formula proposed in this paper to evaluate the dynamic effect of wave loads in fatigue analysis for 03 Jacket structures built at increasing water depth under one specific marine condition and provide specific recommendations on the limits of application of quasi-static and dynamic methods in the fatigue analysis of the jacket structures. This research is really necessary because currently, the current standards (API, DnV) only stop at evaluating the dynamic effects of wave loads acting on the Jacket structure in the strength analysis. These standards propose a limit for quasi-static or dynamic analysis based on the "3.0 s or 2.5 s rule" (use the quasi-static method when Tmax≤ 3.0 s or ≤ 2.5 s), and it is advised that they only apply to waters within the North Sea and the Gulf of Mexico. This paper has demonstrated that it is not appropriate to use the specified standards for the North Sea and the Gulf of Mexico to select the method of fatigue analysis of the jacket structure in marine conditions outside the study area of the standard. Hoped that this paper will be a reference for engineers when choosing a fatigue analysis method for jacket structures in specific marine conditions at the location where the jacket structure has been installed. Doi: 10.28991/CEJ-2023-09-02-016 Full Text: PDF